Plasma Process. Polym. 6/2013. Issue 6 (6th June 2013) - Hilt, Florian; Duday, David; Gherardi, Nicolas; Frache, Gilles; Bardon, Julien; Choquet, Patrick
<x xml:space="preserve">Abstract</x> Cover: An original polyphosphate‐based coating was synthesized for the first time by a PECVD process at the atmospheric pressure and the plasma polymer structure considered as a part of a new family of organophosphorus coatings was highlighted. Further details can be found in the article by Florian Hilt et al. on page 556. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>